A DIFUSÃO DO APRENDIZADO DE MERCADO NAS ORGANIZAÇÕES: UM FATOR DE COMPETITIVIDADE - Campos, Celso José de (Revista de Contabilidade do Mestrado em Ciências Contábeis da UERJ, 2004)
Resumo Este artigo descreve a necessidade do aprendizado de mercado como fator de sobrevivência organizacional. Isso significa assumir uma nova postura: gerenciar a organização voltada para o seu mercado. A condição “organização orientada para o mercado" é uma expressão que descreve uma cultura organizacional dirigida à criação de valor superior para o cliente, sendo este o objetivo principal da organização. Nesse caso, a meta de valor superior para o cliente domina todo o pensamento sobre o negócio: que mercados atender e com que produtos ou serviços. A razão principal desse artigo é a de identificar qual seria o nível de aprendizado de mercado a ser adotado na organização para agregar esse valor superior ao consumidor-alvo, caracterizando-se, aí, uma ampliação dos estudos de Marketing. Discorre-se ainda sobre as diversas formas de ocorrer a difusão do aprendizado de mercado nas organizações, como também as possíveis resistências internas a qualquer tipo de aprendizado organizacional. Palavras-chave: Competitividade; Organização Aprendiz; Cultura Organizacional ABSTRACT ]The central idea of the work is that of increasing the value of the learning as the decisive factor and of high competitiveness for the healthy survival of the organization, this being the only alternative solution for confronting this turbulent scenario. In this way, it is emphasized that the alignment with the environment implies that the organization must possess the potential to learn, as well as, to unlearn and to re-learn collectively, which renders the essence of the managerial role a facilitator for learning processes. Within this important perspective, the study proposes to rethink the question of human work which, with the advent of new technologies, reinforces the hopes containing greater sigfnificance. This, of course, demands more technical qualification and a greater level of responsibility from the work force. However, the study takes us to the alternative of defining an international competitive pattern, through the need of finding technologies which permit us to incorporate creatively experiments which were successful in the dynamic centers of world capitalism. In this work we can also verify that the forms of management, which prevents the firms from competing innovatively in the world market, must be urgently changed, for the difficulties inmaking changes in this country are less cultural than political and the cultural dimension must be large and competently administered. Finally, it is suggested, depending on the identified situation, to use intervening strategies , which will facilitate the definitive implantation of the Learning Organization Model. keywords: Competitiviness; Learning Organization; Organizational Culture